Magnetic Adhesion in Wall Climbing Robots using varied Electromagnet Arrangements - J. Florence Gnana Poovathy; E. Sathish; Alapati Lakshmi Viswanath; Nirmala Paramanandham (Journal of Robotics and Control (JRC), 2022)
The improvements and innovations in the field of robotics have given a great opportunity to perform tasks that are hazardous for humans to perform. For example, robots can be used for working on high-storied buildings, inspection on ferromagnetic surfaces, painting and maintenance of buildings, surveillance purposes, etc., at the outset, to carry out any operation on vertical surfaces, which may be quite hazardous and time-consuming as well, wall climbing robots (WCRs) can be deployed. The method of adhesion determines the stability of the robot on the wall, be it smooth or coarse. Using magnets to bring about magnetic adhesion would be advantageous when the robot is maneuvered over iron or steel surfaces, typically, to clean boilers, etc., This paper presents the different ways of placements of the magnets, both permanent and electromagnets, in order to introduce adequate magnetic adhesion that would cease the robot from toppling down while encountering an obstacle. This work proposes two methods of arrangement of magnets: square and diamond. Four electromagnets when arranged in array formation with 5000 windings of thin copper coil, generated a magnetic field force of approximately 150 N when 50 A of current is passed. By and large, around 35 N to 40 N is the suction force that would be sufficient to stick the WCR of 2kg on the wall, while using a suction chamber instead of electromagnets. Other methods of placing the magnets such as square and diamond are studied and compared as well using FEMM. Hence arranging the 4 electromagnets in array formation gives an adhesion pressure sufficient to hold and move the WCR, over the vertical wall against gravity.